Desertification in Africa, Asia and Australia: Human Impact or Variability? - Williams, Martin (Annals of Arid Zone, 2016)
Desertification is currently defined as: ’land degradation in arid, semi-arid and dry sub-humid areas resulting from various factors, including climatic variations and human activities’ (UNEP, 1992), This definition highlights how difficult it can be to distinguish between the relative intluence of climatic variations and human activities when assessing the causes of desertification. Examples drawn from Africa, Asia and Australia show that land degradation in dry areas is onen far more complex than is first apparent and that great care is needed when attributing probable causes. Sustainable land use in such regions is possible provided some fundamental prerequisites are accepted and implemented by the societies Â·concerned.